Buah Rambutan untuk Cegah Anemia pada Ibu Hamil di BPM Muzilatul Nisma - Sinulingga, Selpyani; Jayanti, Ova (3031-8572, 2023)
Aromatherapy is a healing therapy that uses pure essential oils distilled from various parts of plants, flowers, and trees, each of which has a therapeutic effect. A kind of aromatherapy preparation is aromatherapy candles. Aromatherapy candles are objects that can have a calming effect. Essential oil from lavender flower extract as aromatherapy has a relaxing, anti-neuro depressive and sedative effect which is beneficial for pregnant women who experience insomnia, reduces anxiety levels, and increases alertness levels. This therapy is recommended for pregnant women to help minimize discomfort during pregnancy, especially to reduce sleep disturbance problems. The purpose of this activity is to increase knowledge about the benefits of aromatherapy candles to improve the sleep quality of pregnant women. The target of this activity is pregnant women in the second and third trimesters. The form of activity is in the form of carrying out a pre-test, providing education by giving leaflets, and carrying out a post-test. The results obtained are that there is an increase in knowledge of 28.85%. This educational activity is expected to increase the feeling of comfort and improve the quality of sleep in mothers during pregnancy and support the realization of a safe and comfortable pregnancy.